2012
DOI: 10.1101/gad.204602.112
|View full text |Cite
|
Sign up to set email alerts
|

FUS binds the CTD of RNA polymerase II and regulates its phosphorylation at Ser2

Abstract: Mutations in the RNA-binding protein FUS (fused in sarcoma)/TLS have been shown to cause the neurodegenerative disease amyotrophic lateral sclerosis (ALS), but the normal role of FUS is incompletely understood. We found that FUS binds the C-terminal domain (CTD) of RNA polymerase II (RNAP2) and prevents inappropriate hyperphosphorylation of Ser2 in the RNAP2 CTD at thousands of human genes. The loss of FUS leads to RNAP2 accumulation at the transcription start site and a shift in mRNA isoform expression toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
288
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(316 citation statements)
references
References 23 publications
26
288
2
Order By: Relevance
“…These effects could reflect mechanistically changes in the activity of FUS-interacting proteins; e.g., transcription factors TFIID and RNAP II, splicing factor SRSF10 (Tan and Manley 2009), and/or decreased occupancy on target RNA/DNA sequences (Ishigaki et al 2012;Rogelj et al 2012). Indeed, changes in phosphorylation of the RNAP II large subunit regulatory domain, the C-terminal domain (CTD), have been reported in both FUS knockdown cells and ALS patient fibroblasts, leading to global changes in gene expression (Schwartz et al 2012; and consistent with the known roles of the CTD in transcription and mRNA processing (for review, see Hsin and Manley 2012). However, changes in gene expression resulting solely from reduced levels of nuclear FUS are insufficient to explain fully changes that occur in the presence of ALS mutant FUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects could reflect mechanistically changes in the activity of FUS-interacting proteins; e.g., transcription factors TFIID and RNAP II, splicing factor SRSF10 (Tan and Manley 2009), and/or decreased occupancy on target RNA/DNA sequences (Ishigaki et al 2012;Rogelj et al 2012). Indeed, changes in phosphorylation of the RNAP II large subunit regulatory domain, the C-terminal domain (CTD), have been reported in both FUS knockdown cells and ALS patient fibroblasts, leading to global changes in gene expression (Schwartz et al 2012; and consistent with the known roles of the CTD in transcription and mRNA processing (for review, see Hsin and Manley 2012). However, changes in gene expression resulting solely from reduced levels of nuclear FUS are insufficient to explain fully changes that occur in the presence of ALS mutant FUS.…”
Section: Discussionmentioning
confidence: 99%
“…TET proteins share similar domain organization and copurify or interact with transcription factors (TFIID and RNA polymerase II [RNAP II]) (Bertolotti et al 1996;Law et al 2006;Kwon et al 2013) on the one hand and the spliceosome and SR protein-splicing factors (Yang et al 1998;Rappsilber et al 2002;Zhou et al 2002;Meissner et al 2003;Leichter et al 2011) on the other, suggesting possible roles in coupling transcription and splicing. Considerable evidence implicates TET proteins in splicing control in vivo (Paronetto et al 2011;Blechingberg et al 2012), and FUS was shown to enhance RNAP II transcription while repressing RNAP III transcription in vitro (Tan and Manley 2010) and increase RNAP II phosphorylation, and thereby transcription elongation, in vivo (Schwartz et al 2012). However, the relationship between FUS protein function and ALS pathology has yet to be elucidated.…”
mentioning
confidence: 99%
“…In keeping with the latter, FUS functions in both the soluble nuclear and chromatin fractions. In the chromatin fraction, it binds to the C-terminal domain of RNA Pol II and modulates its phosphorylation on Serine 2, which helps to regulate the transcription of certain genes (20,21). FUS also colocalizes with active (serine 2 phosphorylated) RNA Pol II in undamaged cells (22).…”
Section: Depletion Of Fus and Tdp43 Leads To Excessive Transcription mentioning
confidence: 99%
“…FUS has been implicated in transcriptional and posttranscriptional regulation of gene expression (21)(22)(23)(24)(25)(26). We therefore asked whether changes in gene-expression patterns in CAG-FUS WT and CAG-FUS R521G mice explain both the similarities and differences in the behavioral and cellular phenotypes of the wild-type and mutant transgenic mice.…”
Section: Development Of Cre-inducible Transgenic Mice Globally Overexmentioning
confidence: 99%